2015
DOI: 10.1038/hdy.2014.122
|View full text |Cite
|
Sign up to set email alerts
|

A strong response to selection on mass-independent maximal metabolic rate without a correlated response in basal metabolic rate

Abstract: Metabolic rates are correlated with many aspects of ecology, but how selection on different aspects of metabolic rates affects their mutual evolution is poorly understood. Using laboratory mice, we artificially selected for high maximal mass-independent metabolic rate (MMR) without direct selection on mass-independent basal metabolic rate (BMR). Then we tested for responses to selection in MMR and correlated responses to selection in BMR. In other lines, we antagonistically selected for mice with a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…However, even if BMR were increased in that study, interpretation of the result would be unclear, because V O 2 swim was measured at 258C and resulted in hypothermia (about 78C [38]), so the selected trait certainly comprised a large component of thermogenesis. Finally, a recent report showed no significant increase in BMR after eight generations of selection for high maximum forced-running V O 2 , even though quantitative genetic analyses performed within the framework of the same experiment showed that both of the traits are heritable and genetically correlated [17]. The lack of change in BMR in this case could simply be due to premature termination of this selection experiment.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, even if BMR were increased in that study, interpretation of the result would be unclear, because V O 2 swim was measured at 258C and resulted in hypothermia (about 78C [38]), so the selected trait certainly comprised a large component of thermogenesis. Finally, a recent report showed no significant increase in BMR after eight generations of selection for high maximum forced-running V O 2 , even though quantitative genetic analyses performed within the framework of the same experiment showed that both of the traits are heritable and genetically correlated [17]. The lack of change in BMR in this case could simply be due to premature termination of this selection experiment.…”
Section: Discussionmentioning
confidence: 69%
“…According to the 'aerobic capacity model'-one of the main hypotheses-high BMR in endotherms evolved as a correlated response to selection for increased locomotor performance fuelled by aerobic metabolism [18]. Testing the basic assumption of the model-that BMR is positively correlated with aerobic capacity (maximum rate of oxygen consumption)-has been a motivation for many comparative, experimental, quantitative genetic and conceptual studies, but the issue is not resolved (recent reviews: [13,17,19,20]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the other end of the continuum lie laboratory-based artificial selection experiments, many of which have been conducted with rodents (156,187,211). Some of the examples we find most compelling involve replicated selection at the levels of behavior or whole animal physiological performance.…”
Section: Insights Into Evolutionary Pattern and Processmentioning
confidence: 95%
“…Selection experiments are an excellent way to probe the interrelations among traits, including complex traits, because one can atomize an organism to the desired level, impose selection at that level on a trait of interest, and observe correlated cross-generational changes in other traits (58,60,66,187). They are a good way to test specific hypotheses about putative trade-offs (61) and constraints on the way organisms can evolve (e.g., 205,206,211). In particular, they can be a powerful way to demonstrate mechanism, i.e., how organisms work (58,60).…”
Section: Insights Into Evolutionary Pattern and Processmentioning
confidence: 99%